Short-term Regulation of Visfatin Release in vivo by Oral Lipid Ingestion and in vitro by Fatty Acid Stimulation - Karrasch, T.; Leszczak, S.; Bala, M.; Ober, I.; Martin, J.; Schmid, A.; Kopp, A.; Schaffler, A. (Experimental and Clinical Endocrinology & Diabetes, 2014)
Visfatin represents a new adipokine secreted by visceral adipose tissue and possibly regulating insulin sensitivity. Data on the regulation of visfatin are sparse and contradictory. Our study investigates the regulation of serum visfatin concentrations in healthy and non-diabetic subjects in response to the ingestion of a newly developed oral lipid solution (OLI) in vivo. Furthermore, the effects of a broad spectrum of fatty acids on adipocytic visfatin release were investigated in vitro.100 (42 male and 58 female) healthy volunteers were included in the study. Anthropometric and laboratory parameters (lipoproteins, glucose, insulin, C-peptide) were measured after an overnight fast at 0 h and 2 h, 4 h, and 6 h after OLI. 3T3-L1 preadipocytes were differentiated into mature adipocytes and stimulated with increasing doses of 10 different fatty acids, and the release of visfatin into the supernatants was measured by ELISA.Serum triglycerides significantly rose after OLI. This was accompanied by a significant decrease of glucose, insulin and C-peptide. Serum visfatin levels significantly decreased after OLI. Fasting visfatin levels were negatively correlated with fasting glucose levels. Of the 5 saturated fatty acids tested, only palmitic acid exerted significant effects by strongly downregulating visfatin release by about 66%. The mono-unsaturated fatty acids palmitoleic acid and oleic acid exerted opposite effects decreasing/increasing visfatin release, respectively. Both of the poly-unsaturated fatty acids linoleic acid and arachidonic acid decreased visfatin release.Oral lipid ingestion is a physiological regulator of systemic visfatin release. Fatty acids differentially regulate visfatin release in vitro.
Keywords: visfatin; oral lipid load test; adipose tissue; adipokine; fatty acid